CKD-MBD after kidney transplantation - Wesseling-Perry, Katherine (Springer-Verlag, 2011)
Successful kidney transplantation corrects many of the metabolic abnormalities associated with chronic kidney disease (CKD); however, skeletal and cardiovascular morbidity remain prevalent in pediatric kidney transplant recipients and current recommendations from the Kidney Disease Improving Global Outcomes (KDIGO) working group suggest that bone disease—including turnover, mineralization, volume, linear growth, and strength—as well as cardiovascular disease be evaluated in all patients with CKD. Although few studies have examined bone histology after renal transplantation, current data suggest that bone turnover and mineralization are altered in the majority of patients and that biochemical parameters are poor predictors of bone histology in this population. Dual energy X-ray absorptiometry (DXA) scanning, although widely performed, has significant limitations in the pediatric transplant population and values have not been shown to correlate with fracture risk; thus, DXA is not recommended as a tool for the assessment of bone density. Newer imaging techniques, including computed tomography (quantitative CT (QCT), peripheral QCT (pQCT), high resolution pQCT (HR-pQCT) and magnetic resonance imaging (MRI)), which provide volumetric assessments of bone density and are able to discriminate bone microarchitecture, show promise in the assessment of bone strength; however, future studies are needed to define the value of these techniques in the diagnosis and treatment of renal osteodystrophy in pediatric renal transplant recipients.